Identification and Validation of Candidate Genes Involved in Fatty Acid Content in Oil Palm by Genome-Wide Association Analysis - Xia, Wei; Luo, Tingting; Dou, Yajing; Zhang, Wei; Mason, Annaliese S.; Huang, Dongyi; Huang, Xiaolong; Tang, Wenqi; Wang, Jihua; Zhang, Chunyu; Xiao, Yong (Frontiers in Plant Science, 2019)
Oil palm (Elaeis guineensis) is the highest yielding oil crop per unit area worldwide, but its oil is considered unhealthy for human consumption due to its high palmitic acid content (C16:0). In order to facilitate breeding for fatty acid content in oil palm, genome-wide association analysis (GWAS) was used to identify and validate single-nucleotide polymorphism (SNP) markers and underlying candidate genes associated with fatty acid content in a diversity panel of 200 oil palm individuals. A total of 1,261,501 SNP markers previously developed using SLAF-seq (specific locus amplified fragment sequencing) were used for GWAS. Based on this analysis, 62 SNP markers were significantly associated with fatty acid composition, and 223 candidate genes were identified in the flanking regions of these SNPs. We found one gene (acyl-ACP thioesterase B genes) that was involved in fatty acid biosynthesis and that was associated with high palmitic acid content in the mesocarp. Over-expression of this gene caused a significant increase in palmitic acid content. Our study provides key loci that can be used for breeding oil palm cultivars with low palmitic acid content.